Peroxidación lipídica y estrés laboral en trabajadores de una universidad privada del norte de Perú - Arce Gil , Zhandra (2023)
Objective: To establish the relationship between occupational stress levels and the production of malondialdehyde (MDA), as a product of lipid peroxidation, among workers of Universidad Católica Santo Toribio de Mogrovejo in Chiclayo. Materials and methods: A descriptive, correlational research. The sample consisted of 72 workers, 37 of whom wereprofessors and 35 administrative staff members. Plasma MDA was measured spectrophotometrically by thiobarbituric acid (TBA) reaction. To determine stress, the Occupational Stress Scale, developed by Ivancevich and Matteson in 1989 and adapted by Suárez in 2013, was used. The instrument had 25 items and seven dimensions: organizational climate, organizational structure, organizational territory, technology, leadership influence, lack of cohesion and group support. Results: Twenty-three men and 49 women participated in the research. The mean age was 45.1 years and the standard deviation was 11.33, with a minimum of 25 and a maximum of 68 years. The highest percentage of high occupational stress was observed in the dimensions leadership influence (19.40 %), organizational structure (16.70 %) and organizational territory (16.70 %). A total of 39 workers (54 %), 17 of whom were men and 22 were women, had high levels of MDA—i.e., plasma values higher than 3.94 μM. Spearman’s Rho at 95 % confidence interval showed that the correlation between MDA values and sex, working in another workplace and childcare at home were p = 0.08, p = 0.61 and p = 0.33, respectively; herefore, there was no statistical significance. Conclusions: Out of all workers, 54 % had high plasma levels of MDA. Although no statistically significant correlation was found, the dimensions leadership influence, organizational structure and organizational territory showed high stress levels on the order of 19.40 %, 16.70 % and 16.70 %, respectively.